2018
DOI: 10.1071/mf17247
|View full text |Cite
|
Sign up to set email alerts
|

A sponge of the Cliona viridis complex invades and excavates corals of the Gulf of Mannar, south-eastern India

Abstract: Sponges play an important role in biogenic coral-reef degradation, and it is acknowledged that elevated levels of sponge erosion commonly indicate poor health of coral-reef environments. An increase in the abundance of coral-excavating sponge has been reported from several locations, a development that may move coral-reef carbonate budgets increasingly towards net erosion. The role of coral-excavating sponges on Indian reefs has not been studied in as much detail as elsewhere. The present paper describes the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Corals in the Gulf of Mannar were affected significantly by coral bleaching in 2016 and are under significant stress (Edward et al 2018). Hence, we may interpret the widespread occurrence of overgrowth of the coral excavating sponges as a consequence of the most recent bleaching event occurring in the Gulf of Mannar as evident from recent studies (Ashok et al 2018;Edward et al 2018;Raj et al 2018). Sponges have been reported to be comparatively more capable of 146-(175 ± 1.5)-160.5 × 4 µm 143-(234 ± 1)-188.5 × 1.8 µm 9.2-(9.9 ± 1.2)-10.8 µm 30.5-(47.25 ± 1)-64 µm Benzoni et al 2008 97.5-(160.4 ± 14.6)-308.6 × 5 µm 42.5-(57.4 ± 11)-87.5 × 2.5-(3 ± 0.8)-3.7 µm 137.5-(172.2 ± 40)-242.5 × 2 µm 9-(9.5 ± 3)-10.6 µm 20-(48 ± 10.5)-75 µm thriving in changing climatic conditions and have better regeneration capacity (Miller et al 2010;Runzel 2016).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Corals in the Gulf of Mannar were affected significantly by coral bleaching in 2016 and are under significant stress (Edward et al 2018). Hence, we may interpret the widespread occurrence of overgrowth of the coral excavating sponges as a consequence of the most recent bleaching event occurring in the Gulf of Mannar as evident from recent studies (Ashok et al 2018;Edward et al 2018;Raj et al 2018). Sponges have been reported to be comparatively more capable of 146-(175 ± 1.5)-160.5 × 4 µm 143-(234 ± 1)-188.5 × 1.8 µm 9.2-(9.9 ± 1.2)-10.8 µm 30.5-(47.25 ± 1)-64 µm Benzoni et al 2008 97.5-(160.4 ± 14.6)-308.6 × 5 µm 42.5-(57.4 ± 11)-87.5 × 2.5-(3 ± 0.8)-3.7 µm 137.5-(172.2 ± 40)-242.5 × 2 µm 9-(9.5 ± 3)-10.6 µm 20-(48 ± 10.5)-75 µm thriving in changing climatic conditions and have better regeneration capacity (Miller et al 2010;Runzel 2016).…”
Section: Discussionmentioning
confidence: 80%
“…Turbinaria was the coral genus more covered by the sponge, but it was not the only; in 2008, on the contrary, Benzoni et al found C. (M.) aceratoobtusa to be highly selective for Porites lutea in Yemen; in Mannar, the plate-like life form of this coral might have favoured the sponge overgrowth over it, even if a clear specificity is not demonstrable, considering that infected and not infected colonies may have the same pattern of growth (Table III) In the recent period, records about sponges threating coral reefs are numerous (Table I). Since (Coles & Bolick 2007;Benzoni et al 2008) and to spread out across Indo-Pacific Ocean, enlarging their area of distribution (Ávila & Carballo 2009;Shi et al 2012;de Voogd et al 2013;Rossi et al 2015); in particular, in the most recent period, there is an increasing number of records of T. hoshinota spreading throughout the Indo Pacific negatively affecting coral reefs (Ashok et al 2018;Raj et al 2018;Yang et al 2018;Fromont et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies report the proliferation of sponges in GoM after the 2016 bleaching episode (Raj et al 2018a(Raj et al , 2019Ashok et al 2018;GOMBRT Report 2021) which makes way for opportunistic sponge feeders (Raj et al 2019). Prevalence of coral colonies affected by sponges increased from 13.11 to 17.19% between 2018 and 2021 in the nearby Koswari Island (GOMBRT Report 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Schönberg & Ortiz 2008. Climate change has worsened this competition as the heat-stressed corals are often overpowered by sponges (Ashok et al 2018.…”
Section: Introductionmentioning
confidence: 99%